A Pilot Survey of Potentially Hazardous Trace Elements in the Aquatic Environment Near a Coastal Coal-Fired Power Plant in Taiwan. (July 2019) - Kok, Victor C; Winn, Paul R; Hsieh, Yi-Jer; Chien, Jien-Wen; Yang, Jer-Ming; Yeh, Guang-Perng
Background: A limited number of potentially hazardous trace elements were quantified in the aquatic environment near the world's second largest coal-fired power plant (CFPP) and the coal combustion residual (CCR) disposition sites in Central Taiwan. We postulated that contamination from specific trace elements would be present in the abovementioned aquatic environments. Methods: Cross-sectional sampling of trace elements was first performed between September 24, 2017 and October 3, 2017 outside the CFPP, in the effluent sampled from Changhua, a county south of metropolitan Taichung, and at the historical CCR disposal sites, using the intertidal zone surface seawater and the seawater in an oyster farm as controls. Aqueous samples were collected from 12 locations for analysis of 13 trace elements (Al, As, B, Cd, total Cr, Co, Fe, Pb, Mn, Se, Sr, Tl, and V). We used inductively coupled plasma (ICP) optical emission spectrometry to determine B and Fe levels, and ICP mass spectrometry for all other trace elements. The Spearman rank correlation coefficient (Rho) was calculated to examine the pairwise relation among the trace elements. Results: Al (50% of all samples), B (66.7%), Fe (25%), Mn (50%), Sr (8.3%), and V (25%) were identified as being above the Environmental Protection Agency (EPA) regulation limit. The oyster farm seawater had no concerns. Mn (96.4 μg/L) in the CFPP drainage effluent was 1.9-fold above the regulation limit. Fe, Mn, and V were detected from the cooling channel at 4379, 625, and 11.3 μg/L, respectively. The effluent and water from the areas surrounding the 2 CCR dump sites revealed similar magnitudes of trace element contamination. B is highly correlated with Sr (Rho = 0.94, 95% confidence interval [CI], 0.80-0.98). Meanwhile, Fe is highly correlated with Al (Rho = 0.77), Pb (Rho = 0.71), Co (Rho = 0.75), and V (Rho = 0.84). Conclusions: The EPA must set an explicit regulation limit for aluminum, boron, iron, and strontium in the aquatic environment. This exploratory research will inform policymaking regarding certain trace elements that could potentially have an adverse impact on public health and wildlife.